Characterization of the Biochemical Recurrence Prediction Ability and Progression Correlation of Peroxiredoxins Family in Prostate Cancer Based on Integrating Single‐Cell RNA‐Seq and Bulk RNA‐Seq Cohorts - Shan Tang; Jinchuang Li; Weicheng Tian; Yuanfa Feng; Yulin Deng; Zeheng Tan; Zhaodong Han; Huichan He; Yongding Wu; Chuyang Huang; Keping Ning; Feng Liu; et al. (Cancer Medicine, 2025)
ABSTRACT Introduction The peroxiredoxins (PRDXs) family plays a crucial role in balancing reactive oxygen species (ROS) levels in tumor cells. However, its potential role in prognosis and therapy response of prostate cancer (PCa) remains unknown. Methods In this study, we utilized 2 public single‐cell RNA datasets and 8 bulk‐RNA datasets to investigate the clinical value of six PRDXs family members in PCa. Expression comparison, biochemical recurrence analysis, and therapy response analysis were measured. Pathway enrichments were utilized to predict the potential down‐stream pathway it may involve. In vitro experiments were used to validate the function of PRDX5 in the progression of castration‐resistant prostate cancer (CRPC) cell lines. Result Among the PRDXs family, PRDX5 was most related to the advancement of prostate cancer. A nomogram integrating the expression of PRDX5 with clinical features was developed to better predict clinical outcomes in PCa patients compared to 30 published signatures. Immunohistochemistry was used to verify that PRDX5 expression was higher in advanced levels of PCa tissue. Gene Set Enrichment Analysis (GSEA) and pathway predictive analysis revealed that the PRDX5 related genes were mainly relevant to ROS Pathway, Mitochondria‐related functions, cellular respiration, and oxidative phosphorylation. In vitro cell proliferation assays, ROS determination assay, and apoptosis assay together revealed that depletion of PRDX5 induces apoptosis via ROS accumulation in CRPC cells. Moreover, the expression of PRDX5 in CRPC cells also affects the sensitivity to the ARSI therapy. Conclusion This study offers new evidence for determining that the expression of PRDX5 is associated with advanced tumor grade, poor prognosis, and suboptimal response to multiple therapies in PCa within the PRDXs family. Last but not least, our study provides new insights into precision medicine in PCa and provides a reference for further research on PRDX5.